Systematic failures in the development of photovoltaic systems: The case study of Iran's solar energy - Mohammad Mahdi Akhlaghi; Ali Shafiei Alavijeh; Ramin Hosseinalizadeh; Shohreh Nasri; Sepehr Ghazinoory (Energy Strategy Reviews)
Renewables as alternatives to conventional energy systems have been developing very fast in recent years in Iran like in other countries. This growth is rooted in new goals and support policies that are going to facilitate the development and motivate the investors. Among these policies, Feed in Tariffs (FiT) were customized for different renewables. Furthermore, the length of purchase contracts and the FiT calculation method during the contract period were revised. However, because of the lack of experience and fast growth rate, some serious problems such as the shortage of funding and the system failures caused by the weakness of prerequisite standards and infrastructures are predicted in the future. These problems seem to be more critical, especially for PV systems that don't have a long history in Iran. For this purpose, a system dynamic approach was used to investigate the economic, social, and political aspects of this system. Monocentricity of renewable energy support policies has caused any problem to directly or indirectly cause the system to fail. For example, in this study, the lack of a reference laboratory and relevant standards for photovoltaic systems have been investigated. This study aims to investigate how the lack of reference laboratories and non-compliance with relevant standards will hinder the development of photovoltaic systems. To overcome this problem, in addition to strengthening the issues related to standards and laboratories, it is necessary to widen the range of support policies. Parallel support policies will strengthen the photovoltaic system in Iran.